2008
DOI: 10.1002/glia.20638
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the γ‐secretase components presenilin‐1 and nicastrin in activated astrocytes and microglia following traumatic brain injury

Abstract: Gamma-secretase is an aspartyl protease composed of four proteins: presenilin (PS), nicastrin (Nct), APH1, and PEN2. These proteins assemble into a membrane complex that cleaves a variety of substrates within the transmembrane domain. The gamma-secretase cleavage products play an important role in various biological processes such as embryonic development and Alzheimer's disease (AD). The major role of gamma-secretase in brain pathology has been linked to AD and to the production of the amyloid beta-peptide. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 83 publications
(106 reference statements)
0
61
0
Order By: Relevance
“…These data indicated that LPS activates astrocytes, and activated astrocytes released these cytokines. Activation of astrocytes is also known to lead to elevated β-secretase activity [52][53][54] as well as γ-secretase activity [55], consequently increasing Aβ generation. In this present study, we also found that LPS induced an increase of colocated activated astrocytes and amyloid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that LPS activates astrocytes, and activated astrocytes released these cytokines. Activation of astrocytes is also known to lead to elevated β-secretase activity [52][53][54] as well as γ-secretase activity [55], consequently increasing Aβ generation. In this present study, we also found that LPS induced an increase of colocated activated astrocytes and amyloid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that head trauma and ischemia are important factors contributing to AD dementia. PS1 and nicastrin expression have been found to increase in activated microglia and astrocytes following traumatic brain damage, including closed-head injuries, stabbing-related head trauma, and inflammatory insults, indicating enhanced γ-secretase activity in those cells (Nadler et al, 2008). Indeed, treatment with a γ-secretase inhibitor in an experimental stroke model in mice improves outcome by reducing pro-inflammatory leukocyte infiltration, microglial activation, NF-κB activation and hypoxia inducible factor (HIF)-1α signaling (Arumugam et al, 2006Cheng et al, 2014;Park et al, 2011;Park et al, 2013).…”
Section: Stroke and Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Normal astrocytes can degrade Ab, suggesting that abnormal astrocytes damaged by oxidative stress can increase Ab generation and accumulation. Since the major role of b/c-secretase in brain pathology has been linked to AD and to the production of the Ab, b/c-secretase may participate in the cleavage of APP and Ab generation via activation of astrocyte and microglia by oxidative stress (Nadler et al 2008;Rossner et al 2005).…”
Section: Activated Microglia and Astrocyte By Oxidative Damage Up-regmentioning
confidence: 99%